2012
DOI: 10.1002/jor.22091
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi‐kinase inhibitor pazopanib suppresses growth of synovial sarcoma cells through inhibition of the PI3K‐AKT pathway

Abstract: Synovial sarcoma is an aggressive soft tissue sarcoma with only a modest response to conventional cytotoxic agents. In the present study, we evaluated the potential antitumor effects of a novel anti-angiogenesis agent, pazopanib, against synovial sarcoma cells. We found that pazopanib directly inhibited the growth of synovial sarcoma cells by inducing G1 arrest. Multiplex analyses revealed that the PI3K-AKT pathway was highly suppressed in pazopanib-sensitive synovial sarcoma cells. Furthermore, administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…However, there have only been a few reports that have demonstrated the molecular mechanism by which pazopanib inhibits the growth of a variety of tumors [15,36-40]. Kumar used a cell-free assay system to show kinase activity of pazopanib and found that pazopanib had an IC 50 value of 6 μmol/L for inhibiting c-MET activity [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have only been a few reports that have demonstrated the molecular mechanism by which pazopanib inhibits the growth of a variety of tumors [15,36-40]. Kumar used a cell-free assay system to show kinase activity of pazopanib and found that pazopanib had an IC 50 value of 6 μmol/L for inhibiting c-MET activity [15].…”
Section: Discussionmentioning
confidence: 99%
“…5,23,24 Previous studies have indicated another potential factor in the Akt/mTOR pathway: the activation of receptor tyrosine kinases or cytokine receptors. Epidermal growth factor receptor (EGFR), 14,25,26 insulin-like growth factor-1 receptor (IGF1R), 14,27 and plateletderived growth factor receptor a (PDGFRa) 6,28,29 have been proven responsible for Akt/mTOR pathway activation in SS, and some preclinical studies have lent credence to targeting this pathway. 6,29 Clinical trials of molecular targeting drugs also have been undertaken in STS.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR), 14,25,26 insulin-like growth factor-1 receptor (IGF1R), 14,27 and plateletderived growth factor receptor a (PDGFRa) 6,28,29 have been proven responsible for Akt/mTOR pathway activation in SS, and some preclinical studies have lent credence to targeting this pathway. 6,29 Clinical trials of molecular targeting drugs also have been undertaken in STS. Ridaforolimus, an mTOR inhibitor, produced significantly prolonged progression-free survival in a clinical trial targeting advanced STS, 7 although no significant difference was indicated for OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a. It has been reported that pazopanib mainly targets PDGFRα and induces G1/S arrest by inhibition of the PDGFRα–PI3K–Akt pathway in SS cells10. We therefore performed cell cycle analysis using flow cytometry in order to determine the cell cycle status of pazopanib-resistant and parental cells in the presence or absence of pazopanib.…”
Section: Resultsmentioning
confidence: 99%